Pan-London tuberculosis services: a service evaluation - Belling Ruth; McLaren Susan; Boudioni Markella; Woods Leslie (BMC, 2012)
Abstract Background London has the largest proportion of tuberculosis (TB) cases of any western European capital, with almost half of new cases drug-resistant. Prevalence varies considerably between and within boroughs with research suggesting inadequate control of TB transmission in London. Economic pressures may exacerbate the already considerable challenges for service organisation and delivery within this context. This paper presents selected findings from an evaluation of London's TB services' organisation, delivery, professional workforce and skill mix, intended to support development of a strategic framework for a pan-London TB service. These may also interest health service professionals and managers in TB services in the UK, other European cities and countries and in services currently delivered by multiple providers operating independently. Methods Objectives were: 1) To establish how London's TB services are structured and delivered in relation to leadership, management, organisation and delivery, coordination, staffing and support; 2) To identify tools/models for calculating skill mix as a basis for identifying skill mix requirements in delivering TB services across London; 3) To inform a strategic framework for the delivery of a pan-London TB service, which may be applicable to other European cities. The multi-method service audit evaluation comprised documentary analysis, semi-structured interviews with TB service users (n = 10), lead TB health professionals and managers (n = 13) representing London's five sectors and focus groups with TB nurses (n = 8) and non-London network professionals (n = 2). Results Findings showed TB services to be mainly hospital-based, with fewer community-based services. Documentary analysis and professionals' interviews suggested difficulties with early access to services, low suspicion index amongst some GPs and restricted referral routes. Interviews indicated lack of managed accommodation for difficult to treat patients, professional workforce shortages, a need for strategic leadership, nurse-led clinics and structured career paths for TB nurses and few social care/outreach workers to support patients with complex needs. Conclusions This paper has identified key issues relating to London's TB services' organisation, delivery, professional workforce and skill mix. The majority of these present challenges which need to be addressed as part of the future development of a strategic framework for a pan-London TB service. More consistent strategic planning/co-ordination and sharing of best practice is needed, together with a review of pan-London TB workforce development strategy, encompassing changing professional roles, skills development needs and patient pathways. These findings may be relevant with the development of TB services in other European cities.